New Flexible Medical Compact Antenna: Design and Analysis - Yann Mahe; Anne Chousseaud; Marc Brunet; Bruno Froppier (International Journal of Antennas and Propagation)
Some results on embedded antennas for medical wireless communication systems are presented. Medical telemetry can advantageously assist medical diagnostics. For example, you can better locate a diseased area by monitoring temperature inside the human body. In order to establish efficient wireless links in such an environment, a special attention should be paid to the antenna design. It is required to be of a low profile, very small regardless of the working frequency—434 MHz in the ISM band, safe, and cost effective. Design of the as-considered antenna is proposed based on a simple model. The approach has been demonstrated for a compact flexible antenna with a factor of 10 with respect to the half-wave antenna, rolling up inside an ingestible pill. Measured and calculated impedance behaviour and radiation characteristics of the modified patch are determined. Excellent agreement was found between experiment and theory.